Late Holocene coastline and landscape changes to the west of Ephesus, Turkey. (20th January 2019) - Stock, Friederike; Halder, Stefan; Opitz, Stephan; Pint, Anna; Seren, Sirri; Ladstätter, Sabine; Brückner, Helmut
Abstract: Palaeogeographical research regarding coastline and landscape changes has been conducted in the Küçük Menderes graben and the environs of the ancient city of Ephesus in Western Turkey for a few decades. Based on geophysical data, multi-proxy and microfaunal analyses of sediment cores, 14 C-AMS age estimates and diagnostic ceramics, this study presents for the first time results of an area close to the present coastline, where a Byzantine church is located on top of a small hill. The results reveal that this mica schist hill turned into an island during the 2nd/1st millennium BCE. It was reconnected to the mainland via a tombolo during the 5th century CE. Drill cores and geophysical measurements surrounding the hill show massive stone layers which were deposited intentionally during the 5th/6th century CE when the Byzantine church was built. Geophysical images point to wall structures in the surroundings of the hill. The area to the northeast hosts a small harbour site. When the coastline continued to shift further to the west, this site was still connected to the sea by the Küçük Menderes river.